Performance of Between-study Heterogeneity Measures in the Cochrane Library. Issue 6 (November 2018) - Ma, Xiaoyue; Lin, Lifeng; Qu, Zhiyong; Zhu, Motao; Chu, Haitao
Abstract : The growth in comparative effectiveness research and evidence-based medicine has increased attention to systematic reviews and meta-analyses. Meta-analysis synthesizes and contrasts evidence from multiple independent studies to improve statistical efficiency and reduce bias. Assessing heterogeneity is critical for performing a meta-analysis and interpreting results. As a widely used heterogeneity measure, the I 2 statistic quantifies the proportion of total variation across studies that is caused by real differences in effect size. The presence of outlying studies can seriously exaggerate the I 2 statistic. Two alternative heterogeneity measures, the and have been recently proposed to reduce the impact of outlying studies. To evaluate these measures' performance empirically, we applied them to 20, 599 meta-analyses in the Cochrane Library. We found that the and have strong agreement with the I 2, while they are more robust than the I 2 when outlying studies appear. Abstract : Supplemental Digital Content is available in the text.